Jurisprudential criteria of the Supreme Court about the dismissal null - Toyama Miyagusuku, Jorge (2016)
In this article, the authors explain some notions about job security and some general aspects of the nullity of the dismissal (proof of the dismissal null and its causes). Also, they explain the judicial criteria on the nullity of dismissal that have been issued through cassation rulings by the Supreme Court. Among these criteria are union membership or participation in union activities, filing a complaint or participation in processes against the employer, discrimination, and pregnancy.